Political Philosophy A-Z - Pike, Jonathan E. 1965- (Philosophy A-Z : PAZ, 2022)
A comprehensive, up to date and concise guide to one of the most important branches of philosophy.Both topical and historical, Political Philosophy A-Z has entries on Hobbes, Marx, and Rorty, as well as entries which explain what 'contract theory' is, and gives an account of 'multi-culturalism.' This book guides the reader through the intricacies of political theory, enabling them to trace their way through a debate, fixing historical and theoretical points of reference along the way. It is well suited for students studying political philosophy at university. Political Philosophy A-Z links up positions, thinkers and theories without unnecessary technicality. It is a valuable guide to political theorising